SPME as a green sample-preparation technique for the monitoring of phytocannabinoids and endocannabinoids in complex matrices - Katarzyna Woźniczka; Paweł Konieczyński; Alina Plenis; Tomasz Bączek; Anna Roszkowska (Elsevier, 2023)
The endocannabinoid system (ECS), particularly its signaling pathways and ligands, has garnered considerable interest in recent years. Along with clinical work investigating the ECS' functions, including its role in the development of neurological and inflammatory conditions, much research has focused on developing analytical protocols enabling the precise monitoring of the levels and metabolism of the most potent ECS ligands: exogenous phytocannabinoids (PCs) and endogenous cannabinoids (endocannabinoids, ECs). Solid-phase microextraction (SPME) is an advanced, non-exhaustive sample-preparation technique that facilitates the precise and efficient isolation of trace amounts of analytes, thus making it appealing for the analysis of PCs and ECs in complex matrices of plant and animal/human origin. In this paper, we review recent forensic medicine and toxicological studies wherein SPME has been applied to monitor levels of PCs and ECs in complex matrices, determine their effects on organism physiology, and assess their role in the development of several diseases.